BLACK AND WHITE-BOX UNIT TESTING FOR WEB APPLICATIONS - Golіan Nataliіa; Golіan Vira; Afanasieva, Iryna (Bulletin of National Technical University "KhPI". Series: System Analysis, Control and Information Technologies, 2022)
The types of the testing methods were analyzed from the side of development. If changes are made to the code, even minor ones, bugs can appear anywhere in the system. The cost of fixing bugs increases with the time they are discovered. Using effective web testing can prevent unexpected costs. Modern web applications are indeed a place where all the type of the testing is vital for the high-quality product. At the moment, traditional front and back office applications are increasingly moving from desktop computers to web interfaces, so testing web applications is becoming extremely relevant. Thus, learning what to automate and how is an important component of successful web application testing. Web application testing is a software practice that is designed to ensure quality by verifying that the functionality of a particular web application works correctly or according to fixed requirements. Web testing makes it possible to find bugs at any point in time, before release or on a daily basis. On the one hand there are wide range of tools that could be used to pursue this goal by means of using best decisions present for now but on the other hand there are essential advantages and disadvantages present in these tools, which are all in the approach to it, so there are always cons and pros of using one or another. For now, despite on having the ability to test using both black and white box testing it looks like the second one is not the best choice. There are several points on each board for both of them, but black box approach that is being represented with react testing library is more successful and efficient way to cover and application with high- and low-level tests, that could be easily maintained and understood. But white box testing is now the most used decision due to the historic development of the industry. So, it also has some great features and could be chosen to be used on the project, but it should be precise choice with the understanding of all the consequences standing behind.